2023
DOI: 10.1177/19476035231166127
|View full text |Cite
|
Sign up to set email alerts
|

Knee Osteoarthritis: Clinical and MRI Outcomes After Multiple Intra-Articular Injections With Expanded Autologous Adipose-Derived Stromal Cells or Platelet-Rich Plasma

Miguel A. Khoury,
Karim Chamari,
Montassar Tabben
et al.

Abstract: Objective To directly compare clinical and MRI outcomes of multiple intra-articular injections of adipose-derived stromal cells (ASCs) or platelet-rich plasma (PRP) in patients with knee osteoarthritis (OA). Design We retrospectively compared 24-month outcomes in (1) 27 patients receiving 3-monthly intra-articular injections with a total of 43.8 million ASCs and (2) 23 patients receiving 3-monthly injections of 3-ml preparation of PRP. All patients had Kellgren-Lawrence grade 1, 2, or 3 knee OA with failed con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 83 publications
0
2
0
Order By: Relevance
“…We appreciate your comments and concerns and appreciate academically reaching out to us with an elegant letter and genuine interest in our article "Knee Osteoarthritis: Clinical and MRI Outcomes After Multiple Intra-Articular Injections With Expanded Autologous Adipose-Derived Stromal Cells or Platelet-Rich Plasma." 1 We agree with your concerns about the wide variety of platelet-rich plasma preparations and the lack of standardization. Likewise, recent systematic reviews have additionally found an alarming lack of reporting quality of the orthobiologics studies.…”
Section: Dear Editor and Colleaguesmentioning
confidence: 54%
See 1 more Smart Citation
“…We appreciate your comments and concerns and appreciate academically reaching out to us with an elegant letter and genuine interest in our article "Knee Osteoarthritis: Clinical and MRI Outcomes After Multiple Intra-Articular Injections With Expanded Autologous Adipose-Derived Stromal Cells or Platelet-Rich Plasma." 1 We agree with your concerns about the wide variety of platelet-rich plasma preparations and the lack of standardization. Likewise, recent systematic reviews have additionally found an alarming lack of reporting quality of the orthobiologics studies.…”
Section: Dear Editor and Colleaguesmentioning
confidence: 54%
“…We appreciate your comments and concerns and appreciate academically reaching out to us with an elegant letter and genuine interest in our article “Knee Osteoarthritis: Clinical and MRI Outcomes After Multiple Intra-Articular Injections With Expanded Autologous Adipose-Derived Stromal Cells or Platelet-Rich Plasma.” 1…”
mentioning
confidence: 99%
“…Belk et al (2023) reported no difference in outcome scores between PRP and BMAC, but both the PRP and BMAC outcome scores were better than those for patients receiving HA injection 46 . A recent study showed that autologously expanded AT-MSCs are better than PRP, especially at 12-and 24month follow-ups 47 . Bolia et al (2021) compared the clinical efficacy of BMAC and SVF for knee OA 48 based on 10 studies with 472 patients (233 patients with BMAC, 239 patients with SVF).…”
Section: Which Kinds Of Stem Cells Are the Best For Treating Knee Ost...mentioning
confidence: 99%